Synthesis, Characterization, and Electrochemical Performance of Reduced Graphene Oxide-Metal (Cu,Zn)-Oxide Materials - Sugianto Sugianto; Ngurah Made Dharma Putra; Endah F. Rahayu; Wahyu B. Widayatno; Cherly Firdharini; Slamet Priyono; Didik Aryanto (Universitas Pendidikan Indonesia, 2023)
The reduced graphene oxide (rGO) and metal (Cu,Zn)-oxide composites were prepared using a one-step hydrothermal technique. The role of (Cu,Zn)-oxide on the physical and electrochemical properties of the composite was investigated. The composite consists of various shapes of ZnO nanoflowers and micro-spheres, as well as Cu-oxide nanoflakes and octahedron-like shapes. The (Cu,Zn)-oxides were formed in between the rGO layers and observed in the rGO-ZnO, rGO-CuO, and rGO-CuO-ZnO composites. The presence of ZnO, CuO, and rGO within the composite structure is also confirmed by the analyses of crystal structure, microstructure, and surface functional groups. Some excess impurities remaining from the surfactant give considerable differences in the electrochemical performance of the composites. The specific capacitance values of the rGO, rGO-ZnO, rGO-CuO, rGO-(0.5CuO-0.5ZnO), and rGO-(0.25CuO-0.75ZnO) composites are 9.32, 58.53, 54.14, 25.21, and 69.27 F/g, respectively. The formation ofa double metal-oxide structure as well as their insertion into the rGO sheet can significantly improve the electrochemical properties of the supercapacitor.